Role of Classification in Information Services Generation - Seetharama, S. (Journal of Information and Knowledge, 1992)
Mentions the areas of application of the postulates and principles of Ranganathan’s general theory of knowledge classification. Indicates that classification in the sense of organizing concepts is involved in the generation, storage, retrieval, and dissemination of information. especially in designing database, construction of user interests profile, subject description of documents, arrangement and presentation of information, etc. Demonstrates with example, the applications of Ranganathan’s postulates and principles of classification in the preparation of an information analysis and consolidation product.